Impact of cardiac magnetic resonance on the diagnosis and management of patients with cardiomyopathies - Popa Oana-Andreea; Onciul Sebastian; Badea Thedor; Marian Denisa; Rac-Albu Bogdan; Amzulescu Mihaela; Bugeac Claudia; Chiriac Oana; Tomescu Luminița; Gheorghita Valeriu; Roșu Andrei (Romanian Journal of Cardiology)
Cardiac magnetic resonance (CMR) is an essential tool for diagnosis and prognosis in patients with cardiomyopathies. Over the past decades, it has become the gold standard for assessing cardiac function, volumes and mass. In addition, its tissue characterization capabilities, including T1, T2 and T2* mapping and gadolinium enhancement images, allow differentiation between ischemic, inflammatory and infiltrative etiologies of heart disease.